Стійкість проти бурої іржі у комерційних сортів пшениці м’якої озимої з пшенично-житніми транслокаціями - Власенко, В.А.; Осьмачко, О.М.; Бакуменко, О.М. (Фактори експериментальної еволюції організмів, 2013)
Aims. Studying the genetic potential of the Ukrainian commercial cultivars of winter bread wheat domestic and foreign breeding for resistance to brown rust in condition Forest-steppe of Ukraine and the relationship of this disease with yields. Methods. Studies were conducted using field, laboratory and mathematical-statistical methods. Assessment of plant resistance to brown rust of wheat was carried out in the period of maximum development of the disease in the field. Plant resistance was assessed visually as the onset of symptoms. Results. Cultivars – Columbia, Smuglyanka and Zolotokolosa with group resistance to the most common diseases in the Forest-steppe of Ukraine. The greatest value are varieties of wheat-rye translocation 1BL/1RS (Kryzhynka, Kalynova) and 1AL/1RS (Columbia, Smuglyanka, Zolotokolosa). Conclusions. A presence at the cultivars of wheat of bread winter – annual wheat-rye translocation stipulates the increased activity of the immune system of plants. It provides forming of resistance against harmful biotic factors and the best index of the grain-growing productivity.

Key wods: Winter wheat, leaf rust, resistance, yielding capacity.